Pemodelan Matematis Pengaturan Frekuensi Beban Sistem Tenaga Hibrid Turbin Angin-Diesel-PV - Zainal - Abidin (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2020)
Modeling study mathematically analyzes the wind-diesel-PV hybrid system with PI control for load frequency regulation (LFC). To improve the reliability of electricity supply, renewable energy sources such as wind and solar energy are integrated with a diesel power generation system to supply power for isolated areas. Isolated hybrid power system is designed to minimize mismatch between generation and load consumption. Due to unstable wind generation, solar PV sources, and frequent load changes, there are fluctuations in power generation especially in system frequency and voltage. Conventional PI control is used to adjust the system load frequency to make the frequency drift to the allowable range. This article presents a complete mathematical modeling of a system consisting of a wind turbine induction generator unit, a diesel engine synchronous alternator unit and a solar panel (PV) with MPPT (Maximum Power Point Tracking).